REFAG 2014 : proceedings of the IAG Commission 1 Symposium Kirchberg, Luxembourg, 13-17 October, 2014 (International Association of Geodesy symposia, 2017)
This book series is composed of peer-reviewed proceedings of selected symposia organized by the International Association of Geodesy. It deals primarily with topics related to Geodesy as applied to the Earth Sciences : terrestrial reference frame, Earth gravity field, Geodynamics and Earth rotation, Positioning and engineering applications.